Romanian Energy Market Evolution: Towards a Common European Market - Delia Vasilica Rotaru (CES Working Papers, 2013)
This paper is offering a presentation of the energy market in Romania by analyzing its characteristics before and after the fall of communism. Becoming a member of the European Union brought many challenges for our country on different levels, the restructuring of the energy market being one of them. The final aim of the European Union is to create a common European energy market based on sustainable development where the consumers would benefit from quality services and lower prices. An insight on how the market is currently functioning in Romania is provided together with a presentation of the new challenges we have to face in reaching a fully liberalized energy market.
Keywords: D47; L11; O25; 330; liberalization; energy market; European policy; regulation; challenge Romania